(untitled) (European Journal of Social Sciences, 2018)
This article analysis relates to the creation of conditions for the conclusion of the contract.This is the moment when the negotiating parties determine whether there will be a contract or not. This is the stage that in the best case is finalized with the contract signing.Known as the pre-contractual stage, it is considered as the foundation of the contractual relationship.Conduct in good faith at the stage of entering into a contract would also avoid causing potential damages and liability".- The first part gives , of Completion of the contract in good faith, is a legal requirement under the Civil Laë tradition, but unlike the requirement for pre-contractual trust, finds place in the Common Law tradition.In this part of the study, the detailed treatment of the manner of performance of the contract will be set aside, focusing mainly on the obligations that dictate its fulfillment in good faith and the liability incurred in the event of its absence . The second part is concentrated, Contract Interpretation. The third part will be treated as a brief and comparative overview of the common law of Civil Law in the interpretation of the contract, taking into account the main interpretative criteria, to underline the main differences between them. Among all the criteria, the focus will be on trust, which is sanctioned as a special criterion of interpretation by the Civil Law countries. The fourth part analysis the validity of the contract.In this last part of the chapter, I will try to clarify the confusion created between the rules of contract validity and the rules of conduct, as well as the role and impact of the breach of the trust principle in the validity of the contract. Conclusions .Regarding the situations that arise for the damage that comes to the parties from non-fulfillment of obligations and breach of the principle of good faith during the contract's formation, it is necessary to clarify how the type of damage that came during the pre-contractual phase and which interest has failed to realize one of the parties. In fact, this is a genuine duty of the court which, as the case may be, must specify exactly: the responsibility of the parties, the interest that has been violated, the type of damage that has been caused.Keywords: contract law ,internal law ,contractual relation,internal contract interpretation, civil law